1996
DOI: 10.1007/bf01411358
|View full text |Cite
|
Sign up to set email alerts
|

Management of subarachnoid fluid collection in infants based on a long-term follow-up study

Abstract: We report the natural history and management of subarachnoid fluid collections in infants and their management based on a longterm follow-up study in 20 cases. These subarachnoid fluid collections were resolved spontaneously in 17 of 20 patients and only 3 by surgical intervention at the age of 2. In our 20 patients the natural history of subarachnoid fluid collection in infants was benign unless the patients sustained head trauma. Surgical treatment was performed in the cases where a subarachnoid fluid collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
3
25
0
Order By: Relevance
“…Furthermore, other studies have demonstrated that the clinical evolution of some children with benign extracerebral fluid collection in infancy may not be so benign, as they present a higher risk of development of subdural hematomas after minor traumas. 24,28 In accordance with previous reports, 17 our findings suggest that there might be a small subgroup of children initially presenting with benign extracerebral fluid collections in infancy who might actually benefit from early intervention with shunt placement, especially those who present with subdural collections as complications, those with a more significant cognitive impairment, and those who present with some specific risk factors identified in the present study. Some of these factors that have been associated with an increased risk of development of arachnoid cysts, and that might help to select the subgroup of children who might benefit from a more aggressive interventional approach, are: 1) the presence of plagiocephaly, which increased the risk of development of arachnoid cysts by an odds ratio of 4.96 in comparison with children with benign extracerebral fluid collection and without plagiocephaly; and 2) extracerebral fluid collection restricted to the bilateral frontal region, which increased the risk of development of arachnoid cyst by an odds ratio of 5.73 in comparison with children with benign extracerebral collection that extended to multiple lobes (frontotemporal and frontoparietal regions).…”
supporting
confidence: 92%
“…Furthermore, other studies have demonstrated that the clinical evolution of some children with benign extracerebral fluid collection in infancy may not be so benign, as they present a higher risk of development of subdural hematomas after minor traumas. 24,28 In accordance with previous reports, 17 our findings suggest that there might be a small subgroup of children initially presenting with benign extracerebral fluid collections in infancy who might actually benefit from early intervention with shunt placement, especially those who present with subdural collections as complications, those with a more significant cognitive impairment, and those who present with some specific risk factors identified in the present study. Some of these factors that have been associated with an increased risk of development of arachnoid cysts, and that might help to select the subgroup of children who might benefit from a more aggressive interventional approach, are: 1) the presence of plagiocephaly, which increased the risk of development of arachnoid cysts by an odds ratio of 4.96 in comparison with children with benign extracerebral fluid collection and without plagiocephaly; and 2) extracerebral fluid collection restricted to the bilateral frontal region, which increased the risk of development of arachnoid cyst by an odds ratio of 5.73 in comparison with children with benign extracerebral collection that extended to multiple lobes (frontotemporal and frontoparietal regions).…”
supporting
confidence: 92%
“…The incidence of SDH in children with BEH is suspected to be much higher than that seen in the general population, as in one group of children with BEH where the incidence of SDH was 3/20 [1, 13]. Thus, children with BEH seem to be predisposed to developing acute SDH either spontaneously or following minor head trauma [1, 10, 11, 13].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of SDH in children with BEH is suspected to be much higher than that seen in the general population, as in one group of children with BEH where the incidence of SDH was 3/20 [1, 13]. Thus, children with BEH seem to be predisposed to developing acute SDH either spontaneously or following minor head trauma [1, 10, 11, 13]. The etiology of SDH in the setting of BEH is also poorly understood but presumably derives from anatomical and geometric stresses on blood vessels in the enlarged SAS/subdural space [12, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…2,29,31) Acute or chronic subdural hematoma or hygroma are wellknown complications after extracranial shunting, and are considered to be overdrainage-related phenomena. 9,13,26,32,34,37,49) We report two cases of subdural hygroma which occurred in a series of 77 neuroendoscopic procedures and discuss the possible etiologies as well as the surgical and clinical consequences.…”
Section: Introductionmentioning
confidence: 99%